Influence of Energy Consumption and Ecological Footprints on Emission of CO2: A Case from Pakistan - Sajid Khan; Samn Tabassum; Arbab Javed; Samama Javaid; Hafiza Aqsa Zeenat (Review Journal of Social Psychology & Social Works, 2024)
The purpose of this research is to examine the influence of traditional energy, ecological footprint and renewable energy on carbon dioxide (CO2) emission in Pakistan. The regression model was used in this study to analyze the connection between the modeled variables using data from 1990 to 2022. The research discovered that although renewable energy had a negative and large effect on CO2 emissions, conventional energy and the ecological footprint had a significant and beneficial impact. According to this study, the government should discourage conventional energy consumption and promote the consumption of renewable energy in the industrial sector. These are only a few examples of the policies that should be developed for the energy sector.